Dragon fruit (Hylocereus undatus Haw.) jam: Use full, development and characterization - Castro, Juliana Cristina (2021)
The aim of this study was developing formulations of H. undatus Haw. jam with pulp and peel, as well as evaluating nutritional compounds and texture properties through sensorial, instrumental, physical, biochemical and microbiological analyses of the final product. The fruit were selected, sanitized, pulped and grinded, and the formulations with different concentrations of pulp and peel (0 – 100%) were developed and evaluated. Microbiological evaluation showed that the formulations are in accordance with the current legislation. The increase in peel concentration in the jam formulations resulted in better consumer acceptance and higher concentration of phenolic compounds, antioxidants and B complex vitamins, such as B1, B5 and B6. In addition, it gave the jams acceptable and pleasant sensorial characteristics and texture.  Adding peel to the formulations enabled us to make total use of the fruit, with no waste, besides making the coproduct richer in compounds that are beneficial to consumers’ health.